Hubungan Pengetahuan Ibu Dengan Kunjungan Balita ke Posyandu Beringin Kencana Tabunganen Kabupaten Barito Kuala - Irma Wulandari; Lily Citra (HB PRESS, 2019)
The posyandu program was carried out for the benefit of the community, in Indonesia in 2010 toddler visits to the posyandu were still 50%. This study aims to determine the relationship of knowledge of mothers of children under five with toddlers visits to posyandu in Beringin Kencana village, Tabunganen District, Barito Kuala Regency The study is analytical, a type of correlational research with a cross-sectional approach. The population and sample were all mothers who had children under five in Beringin Kencana Village, Tabunganen District, Barito Kuala Regency, which amounted to 72 people. The sampling technique used is total sampling. The data collection instrument uses a questionnaire and observation sheet. The statistical test used was the Chi-Square test. The results of the study were 72 respondents, more than 50% were less knowledgeable (69.5%), knowledgeable (5.5%), knowledgeable enough (25%) about posyandu knowledge, more than 50 % of respondents (52.8%) regularly visit toddlers posyandu. The results of the analysis using the chi square test showed p value: 0.516, the value of p> 0.05, there was no relationship between maternal knowledge of children under five and toddler visits to the posyandu. Based on the results of the study, it is recommended that the Tabunganen Health Center improve information provision by distributing leaflets on the benefits of toddlers posyandu and toddler visits to the posyandu as well as empowering the community by involving the community to become health cadres. To the next researchers are expected to be able to conduct research with different variables